2015
DOI: 10.1111/and.12503
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of methylprednisolone and heparin in ischaemic-reperfusion injury of the rat testicle

Abstract: This study evaluated the therapeutic efficacy of heparin and methylprednisolone in the treatment of ischaemic reperfusion (IR) injury of the testis. Twenty-four male Sprague-Dawley rats were allocated equally into three groups of eight animals each. The left testes were rotated 720° for 2 h in the rats in the torsion-detorsion group. Rats in the treatment groups underwent the same surgical procedure as the torsion-detorsion group but were also given methylprednisolone (group II) or heparin (group III) by an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 28 publications
4
29
0
Order By: Relevance
“…In another study on effects of methylprednisolone and heparin in testicular damage conducted by Mertoğlu et al (2016), it was shown that heparin could not significantly express the antioxidant enzymes SOD, CAT or GSH-Px compared to controls but decreased protein levels of Bax and caspase-3 significantly and anti-apoptotic protein Bcl-2 increased, and totally heparin had a protective role in I/R injury (Mertoğlu et al, 2016). Previous studies have failed to consider the impact of heparin on sperm parameters at testicular I/R injury (Boettcher et al, 2016;Mertoğlu et al, 2016). In contrast to the Mertoğlu et al findings, and consistent with earlier reports, in our study, we demonstrated that heparin can notably increase CAT and GPx activity and decrease MDA levels and leads to reduced oxidative damage.…”
Section: Deepa Et Al In Research On the Impacts Of Heparin On Cell Pmentioning
confidence: 99%
See 4 more Smart Citations
“…In another study on effects of methylprednisolone and heparin in testicular damage conducted by Mertoğlu et al (2016), it was shown that heparin could not significantly express the antioxidant enzymes SOD, CAT or GSH-Px compared to controls but decreased protein levels of Bax and caspase-3 significantly and anti-apoptotic protein Bcl-2 increased, and totally heparin had a protective role in I/R injury (Mertoğlu et al, 2016). Previous studies have failed to consider the impact of heparin on sperm parameters at testicular I/R injury (Boettcher et al, 2016;Mertoğlu et al, 2016). In contrast to the Mertoğlu et al findings, and consistent with earlier reports, in our study, we demonstrated that heparin can notably increase CAT and GPx activity and decrease MDA levels and leads to reduced oxidative damage.…”
Section: Deepa Et Al In Research On the Impacts Of Heparin On Cell Pmentioning
confidence: 99%
“…4. Group 4 (TDH): Testicular torsion/detorsion was induced, and rats intraperitoneally received heparin (800 IU/kg, Alborzdaru) (Mertoğlu et al, 2016). Drug injection in all treatment groups was done 30 min before testicular detorsion.…”
Section: Group 3 (Tdv): Testicular Torsion/detorsion Was Induced Andmentioning
confidence: 99%
See 3 more Smart Citations